2018
DOI: 10.1016/j.jenvman.2018.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Comparing adaptive capacity index across scales: The case of Italy

Abstract: Measuring adaptive capacity as a key component of vulnerability assessments has become one of the most challenging topics in the climate change adaptation context. Numerous approaches, methodologies and conceptualizations have been proposed for analyzing adaptive capacity at different scales. Indicator-based assessments are usually applied to assess and quantify the adaptive capacity for the use of policy makers. Nevertheless, they encompass various implications regarding scale specificity and the robustness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…regional, provincial and municipal levels), are preferable [13,50,51]. Marzi et al (2018) argues that if a composite index is estimated only at a higher administrative or statistical level, the inherent variability of performance at lower administrative levels will be neglected [52]. In addition, Hinkel (2011) suggested that the indicator-based assessments are appropriate at local scale and when systems can be narrowly defined [53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…regional, provincial and municipal levels), are preferable [13,50,51]. Marzi et al (2018) argues that if a composite index is estimated only at a higher administrative or statistical level, the inherent variability of performance at lower administrative levels will be neglected [52]. In addition, Hinkel (2011) suggested that the indicator-based assessments are appropriate at local scale and when systems can be narrowly defined [53].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the variability of resilience measures at lower scales (e.g. municipal level) should be considered in the decision-making process to avoid inadequately informed policies [52]. At the municipal administrative level, most of the indicator-based assessments targeted social vulnerability instead of resilience, including only socioeconomic and demographic features of resilience [54–57].…”
Section: Introductionmentioning
confidence: 99%
“…For ACI, we used the analysis described in depth in [ 69 ]. It combines a set of 10 indicators related to available economic resources (such as provincial GDP, at-risk-of-poverty rate and unemployment), infrastructure, knowledge and technology (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Indicators are used to assess the relative resilience of geographic units through integrating several parameters into one composite index [24]. However, Marzi et al [25] discussed that if an index is used only at a higher administrative level, the inherent variability of unit performance at a lower scale or administrative levels will be neglected. Accordingly, Hinkel [26] suggested that the indicator-based assessments are appropriate at the local scale, where systems are narrowly defined.…”
Section: Urban Resilience Perceptionmentioning
confidence: 99%
“…Accordingly, Hinkel [26] suggested that the indicator-based assessments are appropriate at the local scale, where systems are narrowly defined. Hence, resilience capacity estimations at lower scales (e.g., municipal or district levels) should be considered in the decision-making process and city planning strategies to avoid inadequately informed policies [25].…”
Section: Urban Resilience Perceptionmentioning
confidence: 99%